BETWEEN PUBLIC AND PRIVATE- STATE ENTITY AS A PARTY TO INTERNATIONAL COMMERCIAL ARBITRATION: LESSONS FOR THE REPUBLIC OF UZBEKISTAN - Tojiboev, Akbar; Tojjiboyev, Sarvar; Sharakhmetova, Umida (International Journal of Psychosocial Rehabilitation, 2020)
International commercial arbitration has become an effective mechanism in resolving international commercial disputes owing to the massive increase of commercial interactions between private entities in business world. This article discovered that when States and State entities have different legal personalities, the arbitral tribunals should not expand the arbitral clause to the State itself with respect to the disputes before commercial arbitration. It analyzes the nature of State entities, including important roles of State entities in Uzbekistan and some strategic elements of State entities in international commercial arbitration practice. Furthermore, the article proposes potential solutions on the participation of State entities in international commercial arbitration and provides significant recommendations for further development of international commercial arbitration practice in Uzbekistan.